2020
DOI: 10.1093/cercor/bhaa143
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Psychiatric and Neuropsychological Correlates of Default Mode Network and Dorsal Attention Network Anticorrelation in Children

Abstract: The default mode network (DMN) and dorsal attention network (DAN) demonstrate an intrinsic “anticorrelation” in healthy adults, which is thought to represent the functional segregation between internally and externally directed thought. Reduced segregation of these networks has been proposed as a mechanism for cognitive deficits that occurs in many psychiatric disorders, but this association has rarely been tested in pre-adolescent children. The current analysis used data from the Adolescent Brain Cognitive De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 73 publications
(94 reference statements)
4
15
0
Order By: Relevance
“…While we found that greater DMN-DAN anticorrelation was linked with lower contemporaneous attention problems, we did not find an association between DMN-DAN connectivity and future attention symptoms. The cross-sectional DMN-DAN FC -attention symptom association aligns with work using a previous release of the ABCD data (41). However, this work also stands in contrast with previous studies which have found no association between anticorrelated networks and attention symptoms, albeit in much smaller adult samples (80,81).…”
Section: Discussionsupporting
confidence: 85%
“…While we found that greater DMN-DAN anticorrelation was linked with lower contemporaneous attention problems, we did not find an association between DMN-DAN connectivity and future attention symptoms. The cross-sectional DMN-DAN FC -attention symptom association aligns with work using a previous release of the ABCD data (41). However, this work also stands in contrast with previous studies which have found no association between anticorrelated networks and attention symptoms, albeit in much smaller adult samples (80,81).…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, secondary and exploratory analyses in the present study indicate that stronger CON-DMN connectivity was associated with more severe attention problems for children below poverty, both concurrently and longitudinally. Additionally, another study involving the ABCD dataset showed that weaker anti-correlations between the Dorsal Attention Network and the DMN is associated with more attention problems, and that it is also related to socioeconomic status ( Owens et al, 2020 ). Thus, segregation of the DMN from both the CON and Dorsal Attention Network may be associated with better behavioral outcomes, for children above and below poverty.…”
Section: Discussionmentioning
confidence: 99%
“…Complex cognition, including EF, is hypothesized to partially depend on the segregation of networks located at the top of this functional hierarchy from primary somatosensory activity (Buckner & Krienen, 2013;Mesulam et al, 1998). Indeed, prior studies have reported that the default mode network (DMN; situated at the transmodal end of the axis) segregates from other networks during development, which in turn supports the development of EF (Barber et al, 2013;Sherman et al, 2014;Anderson et al, 2011;Owens et al, 2020). Nonetheless, results remain heterogenous, and the degree to which fundamental properties of cortical hierarchy impacts network development remains unclear (Zhong et al, 2014;Marek et al, 2015;Reinenberg et al, 2015;Dwyer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%